Investigating the impact of Sexual Assault Evidence Collection Kits (SAECKs) as evidence in rape cases prosecuted in the Western Cape High Court between 2012 and 2016 - Malema, Smangele Benedictor (Division of Forensic Medicine and Toxicology, 2020)
Background: The Republic of South Africa (RSA) is facing a rape crisis, with women and children being the most vulnerable. DNA evidence is used to aid in suspect identification and to confirm sexual contact. The collection of biological forensic evidence after a rape incident is routine in RSA, however, its contribution to the outcome of rape cases is still unclear. This study aimed to investigate the use of Sexual Assault Evidence Collection Kits (SAECKs) and their impact on the outcome of rape cases. Methods: Data for this study was collected by conducting a retrospective review of rape cases (n=98) prosecuted and finalised at the Western Cape High Court between 1st January 2012 and 31st December 2016. Court dockets were examined, and data was collected using a set of predefined variables. Backward logistic regression was used to analyse whether there is an association between the accused being found guilty and the use of SAECKs and the presentation of DNA evidence. Main findings: In 61% (n=60/98) of the cases a SAECK was used during the medical examination and a DNA report was generated and available for use in 77% (n=46/60) of these cases. There was a higher conviction rate when a SAECK was used (88%, n=53/60) in comparison to when it was not used (53%, n=8/15). Contrary to our expectation, the use of SAECKs was not found to be positively associated with the conviction when using backward logistic regression. This means the use of a SAECK decreased the odds of finding the defendant guilty of rape, albeit by a small degree (OR=0.196, p-value=0.040). DNA was not associated with the case outcome. The majority of cases were stranger rapes (64%,n=63/98), that occurred outdoors (64%,n=61/95)and mostly in the township locations such as Khayelitsha, Philippi, Nyanga, areas located on the Cape Flats, with only a single perpetrator. Injuries were documented in 50% of the cases (n=49)and almost 48% (n=46/95) of the victims were coerced and threatened with a weapon. Our binary model found only the location of incidence (p-value= 0.006) to be significantly associated with case outcome with an odds ratio of 19.827. Conclusions: The findings from this study are significant as they point out that health care practitioners are adequately trained and equipped to provide quality health care responses and to work effectively with police officers. SAECKs are utilised routinely during rape investigations. However, there are various factors relating to the victim, perpetrator and assault characteristics that influence the judge's verdict. This study raised questions relating to how those factors are measured or weighed and are predictive of case outcome. Although we found no positive associations between the variables investigated (except the location of the incident) and court outcome, future research, including larger sample size, should investigate these variables in order to obtain true significance, especially concerning the use of SAECKs and its impact on the court outcome.